Intra-firm wage inequality and firm performance: first evidence from German linked employer-employee-data - Nils Braakmann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
Economic theory suggests both positive and negative relationships between intra-firm wage inequality and productivity. This paper contributes to the growing empirical literature on this subject. We combine German employer-employee-data for the years 1995-2005 with inequality measures using the whole wage distribution of a firm and rely on dynamic panel-data estimators to control for unobserved heterogeneity, simultaneity problems and possible state dependence. Our results indicate a relative minor influence of intra-firm wage inequality on firm productivity. If anything, they provide some support for a view suggesting that some inequality may be beneficial, while too much leads to a detrimental effect on productivity.
Keywords: J31; M52; 330; Lohnstruktur; Vergütungssystem; Produktivität; Panel; Deutschland